2010
DOI: 10.1002/arch.20352
|View full text |Cite
|
Sign up to set email alerts
|

Adenanthera pavonina trypsin inhibitor retard growth of Anagasta kuehniella (Lepidoptera: Pyralidae)

Abstract: Anagasta kuehniella is a polyphagous pest that feeds on a wide variety of stored products. The possible roles suggested for seed proteinase inhibitors include the function as a part of the plant defensive system against pest via inhibition of their proteolytic enzymes. In this study, a trypsin inhibitor (ApTI) was purified from Adenanthera pavonina seed and was tested for insect growth regulatory effect. The chronic ingestion of ApTI did result in a significant reduction in larval survival and weight. Larval a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 49 publications
4
39
0
3
Order By: Relevance
“…As the proportion of digested food metabolized for energy increases, ECD decreases [47, 48]. Therefore, it is suggested that the reduction in ECD is a likely outcome by undermining the efficiency to convert foodstuffs into growth, perhaps by a diversion of energy from production of biomass into detoxification of BmPI, that is, an increase in costs as reported elsewhere [43, 49]. …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As the proportion of digested food metabolized for energy increases, ECD decreases [47, 48]. Therefore, it is suggested that the reduction in ECD is a likely outcome by undermining the efficiency to convert foodstuffs into growth, perhaps by a diversion of energy from production of biomass into detoxification of BmPI, that is, an increase in costs as reported elsewhere [43, 49]. …”
Section: Resultsmentioning
confidence: 95%
“…Table 4 shows that 0.10% w/w BmPI, incorporated into an artificial diet, decreases the growth, consumption rate, and fecal production of H. armigera larvae. These observations suggest that BmPI acts on intestinal tract and/or interferes with digestive capabilities of the insect or may be an outcome of physiological (postingestive) effects [43]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the search for effective inhibitors applicable in such clinical situations was and still is a challenging topic of tumor therapy-relevant research (Lah et al, 2006;Turk, 2006). In recent years, many proteinase inhibitors have been found in plants, especially in legume seeds Oliva and Sampaio, 2008;Roy and Dutta, 2009;Macedo et al, 2010;Prasad et al, 2010). One major aspect of interest in plant-derived inhibitors is to discover the relationship of structure and specificity or selectivity of these inhibitors for different proteinases enabling structural modifications to target a variety of proteinases, which are significantly involved in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin inhibitors are serine proteinase inhibitors, and high concentrations of such inhibitors are associated with plant resistance to insects, fungi, bacteria, and viruses (Kim et al, 2009, Macedo et al, 2010, Oliva et al, 2011. A successful strategy employing defense proteins in plant breeding requires the investigation of in vitro and in vivo activity against pathogens, determining the partial or full amino acid sequence, and purifying and characterizing the protein of interest (Oliveira and Macedo, 2011).…”
Section: Introductionmentioning
confidence: 99%